2006
DOI: 10.1111/j.1365-2265.2006.02470.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D among unselected medical inpatients and outpatients in Northern Italy

Abstract: We read with interest the recent review article by Mosekilde clearly documenting that vitamin D insufficiency/deficiency is a very common condition among individuals in southern European countries, especially among geriatric patients and those with hip fractures. 1 Because the available data on large population samples in Italy are limited, we would like to offer recent findings from our observational study, in which serum 25-hydroxyvitamin D3 concentrations [25(OH)D] were measured using an automated chemilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…The prevalence of vitamin D deficiency in our population was higher than in several previous studies, which reported prevalences of 12% to 47% [1216]. In contrast, a large Italian study of more than 6000 outpatients and inpatients reported a 52% prevalence of vitamin D deficiency [21]. The higher prevalence of vitamin D deficiency in this study may be related to the northern geographic location of Modena (44°N) which may lead to more indoor activities and less sun exposure.…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence of vitamin D deficiency in our population was higher than in several previous studies, which reported prevalences of 12% to 47% [1216]. In contrast, a large Italian study of more than 6000 outpatients and inpatients reported a 52% prevalence of vitamin D deficiency [21]. The higher prevalence of vitamin D deficiency in this study may be related to the northern geographic location of Modena (44°N) which may lead to more indoor activities and less sun exposure.…”
Section: Discussioncontrasting
confidence: 76%
“…Similar findings have been reported by other investigators among 6403 unselected medical inpatients and outpatients, who attended the laboratory Hospital of Vicenza, a town in Northern Italy. 19 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] We agree with Danielle Grenier that, in addition to heightened efforts by individual health care providers, more rigorous national surveillance is needed to ensure adequate vitamin D intake by pregnant and lactating women and to improve the health and well-being of children and youth. We are pleased that our national data 1 have spurred an interest in defining the vitamin D status of children and adolescents in other countries.…”
Section: Italian Childrenmentioning
confidence: 99%